Pengetahuan dan Sikap Remaja Anak Jalanan tentang Dismenore Primer dan Senam Dismenore di Komunitas Peduli Anak Jalanan Medan - Nur Asnah Sitohang; Diah Lestari Nasution (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
Primary dysmenorrhea is defined as cramping pain in the lower abdomen that occurs at the start of menstruation in the absence of identifiable pelvic disease. It is one of the most common gynecological symptoms among adolescents and adult women with a prevalence of 45%-95%. Overproduction of uterine prostaglandins is the most widely accepted explanation for the pathogenesis. Excessive release of prostaglandins, especially prostaglandin F2 alpha, which is derived from endometrial secretions from menstrual fluid, is believed to cause the condition. Primary dysmenorrhea has different degrees of negative impact on women's physical, psychological and social functioning, which can result in adolescent and adult women being out of school and absent from work. The purpose of this study was to identify the knowledge and attitudes of street children towards primary dysmenorrhea and dysmenorrhea exercise. The research design is descriptive. The sampling technique is total sampling. The number of samples is 45 people. The sample criteria for street children are teenage girls aged 10-18 years, unmarried, already menstruating, can read and write well. Data analysis is descriptive. The results of the study obtained that the majority of street children's knowledge of adolescents was good (53.3%), dysmenorrhea intensity was moderate pain with a score range of 4-7 (68.9%) and adolescent attitudes were negative (71.1%). Knowledge of respondents still needs to be improved to form a positive attitude. It is recommended to the head of KOPA to cooperate with health workers to conduct health education about primary dysmenorrhea on a regular basis to adolescent street children.